Seasonal density and distribution of Octopus tehuelchus in the intertidal of North Patagonia - Storero, Lorena Pia (2013)
The abundance and distribution of coastal cephalopods are strongly influenced by the environmental conditions. This study evaluates the seasonal distribution and density of Octopus tehuelchus in three intertidal environments of San Matı´as Gulf (Patagonia). To estimate and compare density and distribution, monthly transects were carried out, and analysed in relation to the coastlines obtained with satellite images. Densities of O. tehuelchus ranged between 0 and 34 individuals per transect (0–0.11 octopus m22 ), and varied between sites. Islote Lobos (IL) had the highest densities (mean octopus per transect 7.32 + 1.16) followed by El Fuerte (EF) (5.55 + 0.94) and San Antonio Bay (SAB) (3.40 + 0.85). Within each site, octopus densities varied between seasons. The highest densities were observed during warm months (SAB ¼ 5.96, EF ¼ 9.52, IL ¼ 14.15) and the lowest during cold ones (SAB ¼ 1.45, EF ¼ 2.6, IL ¼ 3.32). Octopus tehuelchus showed an aggregated spatial distribution, and the nearest neighbour value varied between 0.21 and 0.83 in SAB, 0.27 and 0.78 in EF and 0.23 and 0.53 in IL. Considering the coast lines, the distribution pattern along the intertidal varied seasonally. During warm months this species is widely distributed throughout the intertidal, from the low-tide line to 300 m (in SAB), 500 m (in EL) and 200 m (in IL). On the contrary, during cold months most individuals were found near the low-tide line. These results may be associated with the availability of shelter in the intertidal and the activity and physiology of this species.